Transisi Kepemimpinan Dalam Alkitab - Jonathan Octavianus (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2016)
As every epoch there are there a transition time, on Old Testament like Moses with Joshua, Joshua selected by God an supported fully by Moses, Conversely Moses have liberally to be changed. Like Elijah to Elisha too.Pattern on New Testament there are an examples of transition time too, like Jesus Christ to His Disciples, an transition from Paul to his successor Timothy. This is a heart and soul a big leader, and shall all leadership owners shepherd in church, Christian institution, etc.Which most be remembered in transition of leadership, that people of God leadership, about who will lead, who continue leadership, like a principle in biblical, hence a role of God, is determinant an anoint man which be selected the absolute God choice and constitute all other, but a succession router leader is which have been selected His own. An can be anointed in front of believers.